O BRINQUEDO COMO FOMENTADOR DAS CULTURAS DA INFÂNCIA NO CONTEXTO ESCOLAR - Larissa Aparecida Trindade dos Santos (Universidade do Oeste Paulista, 2016)
This article presents results of a master's research, conducted at the Graduate Program in the Faculty of Education Science and Technology - UNESP, Presidente Prudente Campus, funded by FAPESP, which has set as its main objective to understand how the toy has been used in the context of children's educational institutions. To this end, it adopted a methodology of qualitative, descriptive-interpretative type and employed methodological tools: observation, semi-structured interviews and bibliographic analysis. The research anchored in the sociology of childhood presented, from the results, that teachers of institutions investigated employing the toy reductionist way, just as material for teaching specific content and skills or even as a resource to attract and entertain children as well devaluing the cultural and historical potential this educational object.